Hypopigmented acquired melanocytic nevi. - Garofalo, L.; Bonifazi, E. (European Journal of Pediatric Dermatology, 2010)
Case report. An 11-year-old child with red hair and green eyes was first observed, with a history of little or nothing infiltrated lesions on the trunk and limbs, arisen gradually in recent years, diagnosed as warts and treated by a doctor with curettage. Physical examination showed on the limbs, and to a lesser extent on the trunk, about twenty lesions of 2-6 mm in diameter, pink, flat or barely raised, with blurred borders, asymptomatic (Fig. 1, 2, red arrows). There were also linear erosions (Fig. 1), results of previous curettage, and some acquired melanocytic nevus (black arrow). The dermoscopic examination of multiple pink lesions (Fig. 3) highlighted in some places little pigmented globules, with a distribution similar to that of normally pigmented melanocytic nevi (Fig. 4). The clinical and dermoscopic findings led to the final diagnosis of hypopigmented acquired melanocytic nevi in a rutile subject.